Chemically grafted graphite nanosheets dispersed in poly(ethylene-glycol) by gamma-radiolysis for enhanced lubrication - Gupta, Bhavana; Panda, Kalpataru; Kumar, Niranjan; Melvin, Ambrose A.; Dash, Sitaram; Tyagi, Ashok Kumar (RSC Advances, 2015)
Graphite nanosheets (Gr-NS) dispersed in poly(ethylene-glycol) (PEG200) medium were subjected to various doses of gamma-irradiation. Hydroxyl functional groups present in PEG are chemically grafted through hydrogen bonding with hydroxyl, carbonyl and carboxylic groups of Gr-NS. The grafting process is driven by the generation of active radicals from solvent radiolysis. Chemical grafting was investigated using X-ray photoelectron spectroscopy (XPS) and Fourier transform infra-red (FTIR) spectroscopy. The results of spectroscopic studies revealed reduction in oxygen functionality of PEG-Gr-NS at higher doses of gamma-irradiation. The gamma-irradiation not only bridges the functionalities between PEG and PEG-Gr-NS but edge and basal plane defects in Gr-NS are further reduced as is evident from Raman analysis. The inter-planar sheet distance in Gr-NS is increased due to intercalated chemical grafting with PEG molecules. The chemical grafting between PEG and Gr-NS and reduction in defects enhance the tribological properties with a decrease of 26% and 32% for the friction coefficient and wear, respectively as compared to PEG alone. The lubrication mechanism is mediated through inter-planar weak forces when PEG is chemically grafted with Gr-NS. The electrostatic interaction of PEG with Gr-NS acts as a molecular bridge thus enhancing the sustainability of tribo-stress. Additionally, in the presence of functionalized PEG-Gr-NS tribo-contact conditions, evidence of deposited graphitic tribo-film was observed from micro-Raman spectroscopy inside the steel wear track. This film further enhanced lubrication mediated through low shear strength interlayer graphite sheets and therefore, antiwear properties were synergistically improved.

Effective noncovalent functionalization of poly(ethylene glycol) to reduced graphene oxidenanosheets through gamma-radiolysis for enhanced lubrication - Gupta, Bhavana; Kumar, Niranjan; Panda, Kalpataru; Melvin, Ambrose A.; Joshi, Shailesh; Dash, Sitaram; Tyagi, Ashok Kumar (Journal of Physical Chemistry C, 2016)
High-quality reduced graphene oxide (rGO) nanosheets (NSs) were synthesized by the oxidation of graphite followed by hydrazine treatment for the reduction of the oxygen functionalities. gamma-Radiolysis was then used for the functionalization of the rGO-NSs with poly(ethylene glycol) 200 (PEG200). The functionalization resulted in the intercalation of PEG200 molecules in rGO through hydrogen bonding between the hydroxyl groups of rGO and the oxygen atoms of PEG200 molecules. This resulted in an increase in the d spacing of the graphene sheets and a decrease in the defect density of the carbon network in the rGO. The friction coefficient and wear of sliding steel surfaces were reduced by 38% and 55%, respectively, when 0.03 mg mL(-1) PEG200-functionalized rGO dispersed in PEG200 was used. The lubrication properties can be described by bipolar interactions between PEG200 and rGO, leading to effective dispersion. Chemical analysis of wear particles showed decomposition of rGO into nanosized graphite domains, as exhibited by mechanical energy produced in tribo-contact. Moreover, these domains formed effective and stable tribofilms on the steel wear tracks that easily sheared under the action of contact stress. This significantly enhanced the antifriction and antiwear properties, resulting in improved oxidation resistance of PEG200 under the tribo-contact. It was found that, at high rGO concentrations, the lubrication efficiency decreased as a result of graphene-graphene intersheet collisions, producing mechanical energy and chemical defects at contact interfaces.